(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Estate planning is about the plans that involves the transfer of estate after somebody passed away. If there are no appropriate estate plan, friends and relatives can spend a lifetime battling over your assets. The estate, which is include cash in bank or cash in hand and properties that own by the deceased likes land and buildings will be distribute to the legal heirs after deduction of funeral expenses and debts for Muslim. The debts are including the debts among human or the debts between God. From the research, they noticed that most of the Malaysia people do not make a will for their estate. It is because in regards to them, the just need to make a will if they have a lot of estate and rich. From time to time, the amount of unclaimed assets keep increasing and this situation have become a significant problem and need to be settled immediately. In regards to this situation, the estate planning is very important in order to make the operation will go smooth without facing any future problems because all the things are related to the law. This paper discussed about a will as an instrument of Muslim estate planning. Nowadays, the will is very important in estate planning because by having the will, we tend not to have problem in the future especially in regards to the process of estate distribution. A will provides for the distribution of certain property owned by the deceased at the time of death, and generally they may dispose of such property in any manner. In fact, the will can change any time before death. They can change for many times. This paper also highlights the importance of will and how to make a will in estate planning. The insight of this paper can contribute to instilling awareness among the public that the wills not just for the wealthy person but everyone can make a wills.